2015
DOI: 10.1080/21645515.2015.1043501
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of adjuvanted vaccines: Methodological considerations

Abstract: Adjuvants mainly interact with the innate immune response and are used to enhance the quantity and quality of the downstream adaptive immune response to vaccine antigens. Establishing the safety of a new adjuvant-antigen combination is achieved through rigorous evaluation that begins in the laboratory, and that continues throughout the vaccine life-cycle. The strategy for the evaluation of safety pre-licensure is guided by the disease profile, vaccine indication, and target population, and it is also influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Baseline outcome rates are a useful part of such an assessment. There is little progress in determining baseline rates in LMIC settings of maternal and neonatal outcomes [4] , [9] , [10] , [11] .…”
Section: Product Considerations - Safety Of Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline outcome rates are a useful part of such an assessment. There is little progress in determining baseline rates in LMIC settings of maternal and neonatal outcomes [4] , [9] , [10] , [11] .…”
Section: Product Considerations - Safety Of Vaccinesmentioning
confidence: 99%
“…This needs to be kept in mind while planning the timelines for enrollment and the attrition rates of the clinical trial or study. Insisting upon identifying, consulting and obtaining additional assent from key decision makers apart from the consent from the pregnant women prior to enrolment would be an easier option for the research team, but this would effectively disempower the woman from making decisions [11] , [12] , [20] .…”
Section: Study Specific Considerations For Immunization In Pregnancy mentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuvant is an option to strengthen and broaden NoV immune responses, and NoV vaccine candidate adjuvanted with aluminum hydroxide and monophosphoryl lipid A has been tested in phase IIb clinical trials [21]. However, due to the local and systemic adverse events associated with adjuvanted vaccines [22], our hypothesis is that in the pediatric NoV vaccine candidate we developed, extremely immunogenic VP6 protein may serve to substitute the external adjuvant. To this end, we have shown that RV VP6 in our combination vaccine has an adjuvant effect on NoV immune responses in vitro and in vivo [14,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…While alum is employed mainly to adsorb the vaccine antigen and as a delivery system [ 21 , 22 ], it has also been described to have some immunomodulatory features [ 23 ]. However, because of the local and systemic adverse effects associated with adjuvanted vaccines [ 24 ], alternatives to current and potentially harmful adjuvants are being considered.…”
Section: Introductionmentioning
confidence: 99%